A high specific energy V s -NiCo 2 S 4 @Ni-MOF self-supporting electrode and its preparation method and application
By coupling NiCo2S4 with Ni-MOF, Vs-NiCo2S4@Ni-MOF self-supporting electrode was prepared, which solved the problems of low energy density and poor MOFs performance of existing supercapacitors, and achieved high specific capacitance and good stability electrodes Material, suitable for positive electrode applications of supercapacitors.
Patent Information
- Application Number
- CN202410633291.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-21
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-05-21
AI Technical Summary
The energy density of existing supercapacitors is limited, which limits its wide application in practical applications. The conductivity of metal oxide frames (MOFs) is low and the reaction kinetics are slow, resulting in poor specific capacity and rate performance.
Through continuous hydrothermal and chemical reduction treatment methods, a sulfur vacancy-modified Vs-NiCo2S4@Ni-MOF self-supporting electrode material was prepared. This material couples NiCo2S4 with Ni-MOF to form a core-shell structure with high specific capacitance and good cycle stability. , the preparation of Vs-NiCo2S4@Ni-MOF was realized.
The specific capacitance of Vs-NiCo2S4@Ni-MOF electrode material is 2.5 times that of simple NiCo2S4 and 2.9 times that of simple Ni-MOF. It has good stability performance. After 10,000 rounds of testing, it still has a capacity retention rate of 81%, which shows that Significant electrochemical performance improvement.
Smart Images

Figure CN118430988B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of electrochemical technology, and in particular to a high specific energy V s -NiCo2S4@Ni-MOF self-supporting electrode and its preparation method and application. Background Art
[0002] With the gradual depletion of petroleum energy and the intensification of environmental problems, clean and renewable alternative energy sources are in urgent need of exploration and development. These clean energy sources such as solar energy, electrical energy, tidal energy, etc. require high-performance energy storage devices to store. Therefore, the development of high-performance energy storage and conversion devices is imminent. The research of various devices such as lithium ion, sodium ion, zinc ion, fuel cells and supercapacitors has aroused widespread interest. Supercapacitors have become a new type of energy storage and conversion system that has attracted much attention in recent decades due to their advantages such as high power density, fast charge and discharge performance and long cycle stability, as well as one of the most promising candidates in high-power applications such as hybrid vehicles, portable electronics, digital communications and renewable energy systems. However, a major bottleneck that hinders more practical applications of existing supercapacitors is their low energy density. To address this problem, designing and synthesizing electrode materials with hierarchical structures is usually an effective way to improve electrochemical performance. This structure consists of multiple components, which synergistically enhance the properties of micro-nano materials and bring additional benefits such as improved stability and anti-aggregation. In addition, the presence of hierarchical structures is conducive to higher specific capacitance and good cycle stability. The hierarchical structure can not only serve as an ion buffer to maintain the supply of electrolyte ions and ensure sufficient Faraday reaction for energy storage, but also provide more diffusion channels, shorten the diffusion distance of electrolyte ions, and ensure that there are enough electrolyte ions in contact with the inner and outer surfaces of the electrode material, further improving the overall specific capacity and energy density of the material.
[0003] Compared with NiCo2O4, spinel NiCo2S4 has attracted more and more attention due to its excellent electrochemical performance and has become a new research hotspot. In the NiCo2S4 structure, replacing oxygen with sulfur can elongate the chemical bonds, thereby producing a more flexible structure, making it easier for electrons to transfer in this tuned structure. Secondly, it exhibits a variety of oxide states and can produce rich redox reactions, which further helps to enhance the electrochemical performance of supercapacitors [YPGao, KJHuang, et al.NiCo2S4 materials for supercapacitor applications[J].Chemistry Asian Journal, 2017, 12(16): 1969-1984]. In particular, NiCo2S4 not only has higher electrochemical activity and specific capacitance than single metal sulfides, but also has a conductivity that is 2 orders of magnitude higher than NiCo2O4, while the conductivity of NiCo2O4 is 2 orders of magnitude higher than that of Ni oxide and Co oxide. These attractive properties are of great benefit for the development of high-performance, especially high-rate supercapacitors. In addition, introducing defects (sulfur vacancies, etc.) into electrode materials can increase the active sites on the surface of the nanostructure, reduce the Gibbs free energy of the surface reaction, thereby improving the utilization rate of the electrochemical surface area and making the redox reaction more sufficient [M. Kandasamy, S. Sahoo, SK Nayak, et al. Recent advances in engineered metal oxide nanostructures for supercapacitor applications: Experimental and theoretical aspects [J]. Journal of Materials Chemistry A, 2021, 9 (33): 17643-17700]. Since the electronegativity of sulfur is lower than that of oxygen, transition metal sulfides are more likely to form vacancies than transition metal oxides [YPLiu, YXWen, YNZhang, et al. Reduced CoNi2S4 nanosheets decorated by sulfur vacancies with enhanced electrochemical performance for asymmetric supercapacitors [J]. Science China-Materials, 2020, 63 (7): 1216-1226].
[0004] Metal-organic frameworks (MOFs) are composed of coordinated metals and organic ligands. Due to their controllable structure and composition, they have always been one of the research hotspots. Currently, MOFs with redox-active metal ions have been widely used as supercapacitor electrode materials. However, MOFs have low conductivity and slow reaction kinetics, which may lead to unsatisfactory specific capacity and rate performance. Therefore, it is of great significance to couple NiCo2S4 with MOFs materials to construct a new electrode material with high specific capacitance and good cycle stability. Summary of the invention
[0005] The present invention aims to provide a high specific energy V s -NiCo2S4@Ni-MOF self-supporting electrode and its preparation method and application, the present invention prepares sulfur vacancy modified V by continuous hydrothermal and chemical reduction treatment s -NiCo2S4@Ni-MOF self-supporting electrode material, which is firmly anchored on the surface of the nickel mesh to form a high-performance self-supporting electrode. After testing, V s -The specific capacitance of NiCo2S4@Ni-MOF electrode material is 2.5 times that of pure NiCo2S4 and 2.9 times that of pure Ni-MOF, achieving the effect of 1+1>2. In addition, it has good stability and still has a capacity retention rate of 81% after 10,000 cycles of testing.
[0006] In order to achieve the above object, the present invention provides the following technical solutions: a high specific energy V s -The preparation method of NiCo2S4@Ni-MOF self-supporting electrode comprises the following steps:
[0007] (1) Using nickel salt, cobalt salt and urea as raw materials, a NiCo-LDH@NF precursor was grown on a substrate by a hydrothermal method;
[0008] (2) The obtained NiCo-LDH@NF precursor was prepared by hydrothermal sulfidation in Na2S·9H2O solution to obtain NiCo2S4@NF;
[0009] (3) The obtained NiCo2S4@NF was treated with hydrazine hydrate to obtain V s -NiCo2S4@NF;
[0010] (4) The obtained V s -NiCo2S4@NF was used as a loading substrate, and Ni(NO3)2·6H2O and terephthalic acid were subjected to hydrothermal reaction in a solvent to obtain the V s -NiCo2S4@Ni-MOF self-supporting electrode.
[0011] Preferably, in step (1), the substrate material is a self-supporting nickel foam substrate.
[0012] Preferably, in step (1), the nickel salt is NiCl2·6H2O; the cobalt salt is CoCl2·6H2O; and the molar ratio of the nickel element in the nickel salt, the cobalt element in the cobalt salt and urea is 1:2:3.
[0013] Preferably, in step (1), the reaction temperature of the hydrothermal method is 120-160° C., and the reaction time is 4-12 h.
[0014] Preferably, in step (2), the reaction temperature of the hydrothermal vulcanization method is 120-160° C., and the reaction time is 4-12 h.
[0015] Preferably, in step (3), the obtained NiCo2S4@NF is treated with hydrazine hydrate to obtain V s -NiCo2S4@NF is specifically: the obtained NiCo2S4@NF is immersed in a N2H4·H2O solution and allowed to stand for 2-12 minutes.
[0016] Preferably, in step (4), the molar volume ratio of Ni(NO3)2·6H2O, terephthalic acid and solvent is 0.3mmol:0.2mmol:25ml; and the solvent is N,N-dimethylformamide.
[0017] Preferably, in step (4), the reaction temperature of the hydrothermal reaction is 120-160° C., and the reaction time is 1-12 h.
[0018] The present invention also provides a high specific energy V prepared by the preparation method. s -NiCo2S4@Ni-MOF self-supporting electrode.
[0019] The present invention also provides a supercapacitor, the raw materials of which include the high specific energy V s -NiCo2S4@Ni-MOF self-supporting electrode.
[0020] Beneficial technical effects:
[0021] The V provided by the present invention s -V in the core-shell structure of NiCo2S4@Ni-MOF self-supporting electrode s-The NiCo2S4 "core" and the Ni-MOF "shell" materials are tightly combined, and the heterogeneous interface formed is conducive to the rapid transfer of electrons and can create abundant redox reaction sites. In addition, the modification of the NiCo2S4 "core" by sulfur vacancies can further enhance the charge transfer rate and reduce the charge transfer resistance, so that the heterogeneous core and shell can achieve the effect of synergistic energy storage. It also has good stability and still has a capacity retention rate of 81% after 10,000 cycles of testing. It can be seen that V s -NiCo2S4@Ni-MOF material has the potential to become the positive electrode of supercapacitors. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0023] Figure 1 SEM comparison of the materials prepared in each step of Example 1 of the present invention and the materials prepared in Comparative Example 1 and Comparative Example 2; wherein a, e are NiCo2S4@NF hollow nanoneedle arrays; b, f are NiCo2S4@Ni-MOF; c, g are V s -NiCo2S4@Ni-MOF; d, h are pure Ni-MOF.
[0024] Figure 2 V prepared in Example 1 of the present invention s -XRD comparison diagram of NiCo2S4@Ni-MOF and pure Ni-MOF material in Comparative Example 1.
[0025] Figure 3 V prepared in Example 1 of the present invention s -TEM images of NiCo2S4@Ni-MOF at different resolutions; a is 200μm, b is 100μm, c is 20μm, and d is 5nm.
[0026] Figure 4 V prepared in Example 1 of the present invention s -Comparison of electrochemical performance of NiCo2S4@Ni-MOF, NiCo2S4@NF, pure Ni-MOF material prepared in Comparative Example 1, and NiCo2S4@Ni-MOF material prepared in Comparative Example 2; where a is 5 mV s -1 Comparison of CV curves under scanning rate; b is 1A g -1 GCD comparison curves of each material at 1-10A g-1 d is the electrochemical impedance spectroscopy (EIS) comparison curve; e and f are V s -CV and GCD curves of NiCo2S4@Ni-MOF electrode material at different scan rates and current densities.
[0027] Figure 5 Assemble the asymmetric supercapacitor V using the material prepared in Example 1 of the present invention s -Electrochemical performance curve of NiCo2S4@Ni-MOF / / AC; a and b are the CV matching diagrams of positive and negative electrodes; c is 5-100mV s -1 CV curves at scan rates; d is 1-20A g -1 GCD curve under current density; e is the rate performance curve and f is the EIS curve.
[0028] Figure 6 a is the Ragone diagram of the asymmetric supercapacitor Vs-NCS@Ni-MOF / / AC assembled with the material prepared in Example 1 of the present invention; b is the Ragone diagram of the asymmetric supercapacitor Vs-NCS@Ni-MOF / / AC assembled with the material prepared in Example 1 of the present invention at 8A g -1 The charge / discharge cycle curve after 10,000 times at the current density. DETAILED DESCRIPTION
[0029] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0030] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0031] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0032] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0033] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0034] The present invention provides a high specific energy V s -The preparation method of NiCo2S4@Ni-MOF self-supporting electrode comprises the following steps:
[0035] (1) Using nickel salt, cobalt salt and urea as raw materials, a NiCo-LDH@NF precursor was grown on a substrate by a hydrothermal method;
[0036] (2) The obtained NiCo-LDH@NF precursor was prepared by hydrothermal sulfidation in Na2S·9H2O solution to obtain NiCo2S4@NF;
[0037] (3) The obtained NiCo2S4@NF was treated with hydrazine hydrate to obtain V s -NiCo2S4@NF;
[0038] (4) The obtained V s -NiCo2S4@NF was used as a loading substrate, and Ni(NO3)2·6H2O and terephthalic acid were subjected to hydrothermal reaction in a solvent to obtain the V s -NiCo2S4@Ni-MOF self-supporting electrode.
[0039] The present invention firstly uses nickel salt, cobalt salt and urea as raw materials and adopts a hydrothermal method to grow a NiCo-LDH@NF precursor on a substrate material.
[0040] In some embodiments, the present invention first dissolves nickel salt, cobalt salt and urea in ultrapure water, and stirs at room temperature for 30 minutes to form a uniform pink transparent solution. Subsequently, the mixed solution is transferred into a stainless steel polytetrafluoroethylene liner reactor, immersed in the substrate material, and the reactor is sealed and placed in an electronic oven for hydrothermal reaction.
[0041] In a preferred embodiment, the substrate material is a self-supporting nickel foam substrate.
[0042] In a preferred embodiment, the nickel salt is NiCl2·6H2O; the cobalt salt is CoCl2·6H2O; the molar ratio of the nickel element in the nickel salt, the cobalt element in the cobalt salt and urea is 1:2:3; the reaction temperature of the hydrothermal method is 120-160°C, and the reaction time is 4-12h.
[0043] Urea provides alkaline reaction conditions in the hydrothermal reaction, which is conducive to the deposition of nickel and cobalt elements. Too little urea will lead to incomplete deposition of nickel and cobalt, and too much urea will lead to uneven deposition. The cobalt element can effectively improve the conductivity and capacity of the material, and the appropriate nickel-cobalt ratio can make the morphology change toward nano needles. Therefore, the present invention is preferably in the above ratio range.
[0044] The present invention also verifies that electrode materials are prepared using other nickel salts and cobalt salts as raw materials, and finds that when the nickel salt and cobalt salt are nickel chloride and cobalt chloride, the chloride ions in the nickel chloride and cobalt chloride help to adjust the morphology toward the nanoneedle morphology. It is difficult for other nickel salts and cobalt salts to achieve this effect.
[0045] A lower hydrothermal reaction temperature will cause the crystal to grow in a specific direction, which helps to form a rod-like structure. A higher hydrothermal reaction temperature will lead to a more stable crystal surface temperature energy and a smaller growth gap between crystal faces, thereby forming a more uniform and smooth surface. Therefore, the present invention preferably uses the above reaction temperature.
[0046] In a preferred embodiment, after the hydrothermal reaction is completed, the present invention further includes cooling to room temperature, washing the obtained sample with deionized water and anhydrous ethanol in turn, removing surface impurities and powder residues by ultrasound, and then vacuum drying overnight to finally obtain a sample labeled as NiCo-LDH@NF precursor.
[0047] After obtaining the NiCo-LDH@NF precursor, the present invention prepares NiCo2S4@NF by hydrothermal sulfidation of the obtained NiCo-LDH@NF precursor in a Na2S·9H2O solution.
[0048] In some embodiments, the specific operation of preparing NiCo2S4@NF by hydrothermal sulfidation of the obtained NiCo-LDH@NF precursor in Na2S·9H2O solution is as follows:
[0049] The NiCo-LDH@NF precursor was immersed in 16 ml (40 mM L -1 ) Na2S·9H2O solution and allowed to stand for 5 min. Then the solution and sample were transferred into a 50 mL stainless steel polytetrafluoroethylene lined reactor, which was sealed and placed in a forced air oven for hydrothermal vulcanization reaction.
[0050] In a preferred embodiment, the reaction temperature of the hydrothermal vulcanization method is 120-160° C., and the reaction time is 4-12 hours.
[0051] A higher hydrothermal vulcanization temperature can make the crystal surface smoother and better maintain the nanoneedle morphology. Too short a vulcanization time will lead to incomplete vulcanization, while too long a vulcanization time will cause significant damage to the morphology. Therefore, the present invention preferably uses the above reaction parameters.
[0052] In a preferred embodiment, after the hydrothermal sulfurization reaction is completed, the present invention further comprises cooling to room temperature, taking out the sample, washing it with deionized water and anhydrous ethanol, and drying it in a vacuum oven at 60° C. for 6 hours, and finally obtaining a sample labeled NiCo2S4@NF.
[0053] After obtaining NiCo2S4@NF, the present invention treats the obtained NiCo2S4@NF with hydrazine hydrate to prepare V s -NiCo2S4@NF. The obtained V s -NiCo2S4@NF as the "core" of the core-shell structure.
[0054] In some embodiments, the obtained NiCo2S4@NF is treated with hydrazine hydrate to obtain V with sulfur vacancies. s -NiCo2S4@NF is specifically: the obtained NiCo2S4@NF is immersed in a N2H4·H2O solution and allowed to stand for 2-12 minutes.
[0055] In a preferred embodiment, the concentration of the N2H4·H2O solution is 1M.
[0056] In a preferred embodiment, after the obtained NiCo2S4@NF is immersed in a N2H4·H2O solution and allowed to stand for 2-12 minutes, the present invention further comprises the steps of washing and drying; the washing and drying are specifically as follows: after the standing, the obtained sample is fully washed with deionized water and anhydrous ethanol, and placed in a vacuum oven at 60°C for 6 hours. The obtained sample is marked as V s -NiCo2S4@NF.
[0057] Get V s -NiCo2S4@NF, the present invention obtains V s -NiCo2S4@NF was used as a loading substrate, and Ni(NO3)2·6H2O and terephthalic acid were subjected to hydrothermal reaction in a solvent to obtain the V s -NiCo2S4@Ni-MOF self-supporting electrode. The present invention uses a hydrothermal method to s -Preparation of Ni MOF “shell” on NiCo2S4 “core”.
[0058] In some embodiments, the hydrothermal reaction is specifically as follows: Ni(NO3)2·6H2O and terephthalic acid are added to the solvent, ultrasonicated, stirred, and then transferred into a 50 ml stainless steel hydrothermal reactor, and a piece of V s -NiCo2S4@NF was used as the loading substrate and the hydrothermal reaction was carried out after sealing.
[0059] In a preferred embodiment, the molar volume ratio of Ni(NO3)2·6H2O, terephthalic acid and solvent is 0.3mmol:0.2mmol:25ml; and the solvent is N,N-dimethylformamide.
[0060] Changing the proportion of terephthalic acid will cause the preferred orientation of the crystal plane of the final product to change, which will have a great impact on the electrochemical properties of the material. Therefore, it is necessary to select a suitable proportion of terephthalic acid.
[0061] In a preferred embodiment, the ultrasonic time is 5 min; the stirring time is 30 min.
[0062] In a preferred embodiment, the reaction temperature of the hydrothermal reaction is 120-160° C., and the reaction time is 1-12 h.
[0063] When the hydrothermal temperature is too low, the Ni MOF formed will have poor crystallinity, while when the temperature is too high, the NiMOF particles produced will be too small and easy to agglomerate. The hydrothermal time can adjust the loading amount of the product. When the hydrothermal time is 3h, the obtained material has the best electrochemical performance.
[0064] In a preferred embodiment, after the hydrothermal reaction is completed, the present invention further comprises cooling to room temperature, then washing the obtained sample with deionized water and anhydrous ethanol, and then drying it in an oven overnight to obtain a final sample, which is marked as V s -NiCo2S4@Ni-MOF.
[0065] The present invention also provides a high specific energy V prepared by the preparation method. s -NiCo2S4@Ni-MOF self-supporting electrode.
[0066] MOFs have low electrical conductivity and slow reaction kinetics, which may lead to unsatisfactory specific capacity and rate performance. NiCo2S4 materials modified with sulfur vacancies are the "core" part of the core-shell structure. Their good electronic properties are more likely to produce synergistic effects with the "shell" material, making the charge storage more efficient and producing higher specific capacitance. Coupling MOFs materials with NiCo2S4 to construct a heterogeneous core-shell structure allows each component to give full play to its own advantages, generate a built-in electric field, and accelerate electron transfer. In addition, additional active sites are also generated due to crystal distortion at the interface, thereby improving the overall electrochemical performance of the material.
[0067] The present invention also provides a supercapacitor, the raw materials of which include the high specific energy V s -NiCo2S4@Ni-MOF self-supporting electrode.
[0068] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.
[0069] The raw materials, reagents and instruments used in the examples can all be obtained through commercial sources.
[0070] Example 1
[0071] Step 1: Weigh 1mmol NiCl2·6H2O, 2mmol CoCl2·6H2O, and 3mmol urea and dissolve them in 30ml ultrapure water. Stir at room temperature for 30min to form a uniform pink transparent solution. Then, transfer the mixed solution into a 30ml stainless steel polytetrafluoroethylene liner reactor, immerse a piece of nickel foam substrate, seal the reactor, place it in an electronic oven at 120℃ for 6h, and after cooling to room temperature, wash the sample with deionized water and anhydrous ethanol in turn, remove surface impurities and powder residues by ultrasound, and then vacuum dry overnight to obtain a sample labeled as NiCo-LDH@NF precursor.
[0072] Step 2: Immerse the obtained NiCo-LDH@NF precursor in 16 ml (40 mM L -1 ) in a Na2S·9H2O solution and allowed to stand for 5 min. Then, the solution and the sample were transferred into a 50 mL stainless steel polytetrafluoroethylene lined reactor, sealed, and placed in a forced air oven at 160 °C for 4 h. After cooling to room temperature, the sample was taken out, washed with deionized water and anhydrous ethanol, and dried in a vacuum oven at 60 °C for 6 h. Finally, the sample was obtained and labeled as NiCo2S4@NF.
[0073] Step 3: The obtained NiCo2S4@NF (1 cm×1 cm) sample was immersed in 1 M N2H4·H2O solution and allowed to stand for 6 min. It was then washed thoroughly with deionized water and anhydrous ethanol and dried in a vacuum oven at 60 °C for 6 h. The obtained sample was marked as V s -NiCo2S4@NF.
[0074] Step 4: Add 0.3mmol Ni(NO3)2·6H2O and 0.2mmol terephthalic acid to 25ml N,N-dimethylformamide, sonicate for 5min, stir for 30min, then transfer to a 50ml stainless steel hydrothermal reactor, and add a piece of V s -NiCo2S4@NF was used as the loading substrate and reacted at 160°C for 3 h after sealing. After cooling to room temperature, the obtained sample was washed with deionized water and anhydrous ethanol, and then dried in an oven overnight to obtain the final sample, which was marked as V s -NiCo2S4@Ni-MOF.
[0075] Comparative Example 1
[0076] 0.3mmol Ni(NO3)2·6H2O and 0.2mmol terephthalic acid were added to 25ml N, N-dimethylformamide, ultrasonicated for 5min, stirred for 30min, and then transferred to a 50ml stainless steel hydrothermal reactor. A self-supporting nickel foam substrate was added at the same time, and the reaction was carried out at 160℃ for 3h after sealing. After cooling to room temperature, the obtained sample was washed with deionized water and anhydrous ethanol, and then dried in an oven overnight to obtain the final sample, which was marked as pure Ni-MOF.
[0077] Comparative Example 2
[0078] The same as Example 1, except that step 3 is omitted. The final sample is labeled as NiCo2S4@Ni-MOF.
[0079] Figure 1 SEM comparison of the materials prepared in each step and the materials prepared in Comparative Examples 1 and 2; a, e are NiCo2S4@NF hollow nanoneedle arrays; b, f are NiCo2S4@Ni-MOF; c, g are V s -NiCo2S4@Ni-MOF and d, h are pure Ni-MOF. It can be clearly seen that Ni-MOF is densely coated on V s -NiCo2S4 and NiCo2S4 nanoneedle surfaces, and the overall nanoneedle core-shell structure outline is still clearly visible.
[0080] Figure 2 For the preparation of V s-XRD comparison of NiCo2S4@Ni-MOF and pure Ni-MOF materials. It shows that the prepared Ni-MOF material is successfully anchored on the surface of Vs-NCS nanocolumns.
[0081] Figure 3 For the preparation of V s -TEM images of NiCo2S4@Ni-MOF hollow nanoneedle materials at different resolutions. It can be clearly seen that the material V s -NiCo2S4@Ni-MOF still has its original hollow nanoneedle structure. After being treated with hydrazine hydrate, there is no obvious structural change and it still maintains its original morphology, indicating that V s -The surface of NiCo2S4 is simply etched, creating a wealth of defects. The Ni-MOF "shell" layer on the outside is clearly visible, with an average thickness of about 64nm, showing a sponge-like loose film structure and with V s -NiCo2S4 cores are tightly bound to form a rich core-shell heterogeneous interface, which is conducive to the rapid transport of electrons and can provide a large number of active sites.
[0082] Figure 4 V s -Comparison of electrochemical performance of NiCo2S4@Ni-MOF, NiCo2S4@Ni-MOF, NiCo2S4@NF and pure Ni-MOF materials, where a is V s -NiCo2S4@Ni-MOF, NiCo2S4@Ni-MOF, pure NiCo2S4@NF and Ni-MOF self-supporting electrode materials at 5mV s -1 Scan rate, CV comparison curves in the potential window of 0-0.65V, all CV curves show a pair of obvious redox peaks, indicating that each electrode is involved in battery-type electrochemical energy storage behavior. s -NiCo2S4@Ni-MOF has the largest CV curve area compared to the other three electrode materials, suggesting that it has the highest redox reaction activity to improve specific capacitance. s -NiCo2S4@Ni-MOF, NiCo2S4@Ni-MOF, pure NiCo2S4@NF and Ni-MOF electrodes at 1Ag -1 , the GCD curve in the 0-0.5V window is as follows Figure 4 As shown in b, the obvious charging and discharging "platform" in the figure represents the battery-type energy storage behavior. s -NiCo2S4@Ni-MOF has the longest discharge time, indicating that it has the largest capacitance. -1The mass specific capacitance calculated according to the corresponding GCD curve is as follows: Figure 4 As shown in c. s -NiCo2S4@Ni-MOF has 2312F g -1 (321.1mAh g -1 ) is much higher than the 916F g of pure NiCo2S4@NF with the same loading. -1 (127.2mAh g -1 ) and 789F g of Ni-MOF -1 (109.5mAh g -1 ), which is also higher than 2094F g of NiCo2S4@Ni-MOF -1 (290.8mAh g -1 ), and at 10A g -1 Time V s -NiCo2S4@Ni-MOF still retains 1432F g -1 (198.9mAh g -1 ) specific capacitance, showing good rate performance. The above test results clearly show that V s -NiCo2S4@Ni-MOF core-shell structure electrode material achieves the effect of 1+1>2, which is because V s -NiCo2S4 core is modified by sulfur vacancies, which improves the electron transfer rate, and the loose and porous characteristics of Ni-MOF shell are conducive to the rapid diffusion of ions. The heterogeneous interface produced by the close combination of the two provides abundant redox reaction sites and can accelerate electron conduction, resulting in a synergistic effect to enhance the charge storage behavior. The equivalent series resistance R of each material can be used to s and the charge transfer resistance R ct The size of further reveals this phenomenon, such as Figure 4 (d) Middle V s -NiCo2S4@Ni-MOF, NiCo2S4@Ni-MOF, pure NiCo2S4@NF and Ni-MOF electrodes are shown in the EIS comparison curves. From the inset of 4(d), it can be clearly observed that V s -NiCo2S4@Ni-MOF electrode has the smallest tangent point with the real axis in the high frequency region and has the smallest semicircle diameter, indicating that it has the smallest equivalent series resistance R s and the charge transfer resistance R ct This is attributed to the improvement of the electronic structure of NiCo2S4 by sulfur vacancies, which effectively reduces the charge transfer resistance and forms a heterogeneous interface with Ni-MOF, which can further accelerate the electron transfer rate and reduce the contact resistance. In addition, V s-NiCo2S4@Ni-MOF is a straight line with a large slope in the low frequency region, indicating that the material has good diffusion performance and tends to ideal capacitance behavior. Vs-V s -The CV and GCD curves of NiCo2S4@Ni-MOF electrode materials at different scan rates and current densities are shown in Figure 2. Figure 4 As shown in (e, f), as the scan rate increases, the redox peak of the CV curve is still visible and its shape remains roughly unchanged, indicating that it has good rate performance and reversible redox reaction.
[0083] Figure 5 For the assembled asymmetric supercapacitor V s -Electrochemical performance curve of NiCo2S4@Ni-MOF / / AC. Figure 5 (a, b) are the CV matching curves of asymmetric devices and the determination of voltage range. The CV effective range of AC materials is set to -1-0V, and V s -NiCo2S4@Ni-MOF’s CV range is set to 0-0.65V. After final testing, V s -NiCo2S4@Ni-MOF / / AC device has an effective range of 0-1.55V. Figure 5 (c, d) are asymmetric devices at 5-100mV s -1 CV and 1-20Ag -1 The GCD curve shows the typical asymmetric supercapacitor characteristics, showing the characteristics of the combined pseudocapacitance and double layer curves. The calculated specific capacitance is shown in Figure 5 (e) As shown, 1Ag -1 The specific capacity can reach 306F g -1 The EIS curve is as follows: Figure 5 As shown in (f), it can be seen that the entire device has small impedance and ideal capacitance behavior.
[0084] Figure 6 To prepare material V s -(Vs-NCS@Ni-MOF / / AC) Ragone plot of NiCo2S4@Ni-MOF assembled asymmetric supercapacitor and at 8Ag -1 The charge / discharge cycle curve after 10,000 times at a current density of 868.4 W / kg -1 The power density reaches 108.8Whkg -1 The energy density is even at 16000Wkg -1 26.3Whkg is still retained -1 In addition, the device is 8Ag -1 After 10,000 cycles of charge and discharge, the curve is as follows Figure 6As shown in (b), it can be seen that even after 10,000 long cycle tests at a higher current density, the capacitance retention rate is still 81% and the coulombic efficiency remains around 100%, which is enough to show that V s -NiCo2S4@Ni-MOF material has the potential to become the positive electrode of supercapacitors.
[0085] Example 2
[0086] Same as Example 1, except that the temperature of the hydrothermal reaction in step 1 is 160°C.
[0087] Example 3
[0088] Same as Example 1, except that the time of the hydrothermal reaction in step 1 is 4 hours.
[0089] Example 4
[0090] Same as Example 1, except that the hydrothermal reaction time in step 1 is 12 h.
[0091] Example 5
[0092] The same as Example 1, except that the temperature of the hydrothermal vulcanization reaction in step 2 is 120°C.
[0093] Example 6
[0094] The same as Example 1, except that the time of the hydrothermal vulcanization reaction in step 2 is 12 hours.
[0095] Example 7
[0096] Same as Example 1, except that the temperature of the hydrothermal reaction in step 4 is 120°C.
[0097] Example 8
[0098] Same as Example 1, except that the standing time in step 3 is 2 min.
[0099] Example 9
[0100] Same as Example 1, except that the standing time in step 3 is 12 min.
[0101] Example 10
[0102] Same as Example 1, except that the time of the hydrothermal reaction in step 4 is 1 h.
[0103] Embodiment 11
[0104] The same as Example 1, except that the time of the hydrothermal reaction in step 4 is 6 hours.
[0105] Example 12
[0106] Same as Example 1, except that the time of the hydrothermal reaction in step 4 is 12 h.
[0107] The V prepared in Examples 2 to 12 s -NiCo2S4@Ni-MOF electrode material was tested for effect verification, and the test results were similar to those in Example 1. s -NiCo2S4@Ni-MOF electrode material has a large specific capacitance, and when it is assembled into a capacitor, it has a small impedance and ideal capacitive behavior.
[0108] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A high specific energy V s -The preparation method of NiCo2S4@Ni-MOF self-supporting electrode is characterized in that: The following steps are involved: (1) Using nickel salt, cobalt salt and urea as raw materials, a NiCo-LDH@NF precursor was grown on a substrate by a hydrothermal method; (2) The obtained NiCo-LDH@NF precursor was prepared by hydrothermal sulfidation in Na2S·9H2O solution to obtain NiCo2S4@NF; (3) The obtained NiCo2S4@NF was treated with hydrazine hydrate to obtain V s -NiCo2S4@NF; (4) The obtained V s -NiCo2S4@NF was used as a loading substrate, and Ni(NO3)2·6H2O and terephthalic acid were subjected to hydrothermal reaction in a solvent to obtain the V s -NiCo2S4@Ni-MOF self-supporting electrode.
2. The preparation method according to claim 1, characterized in that: In step (1), the substrate material is a self-supporting nickel foam substrate.
3. The preparation method according to claim 1, characterized in that: In step (1), the nickel salt is NiCl2·6H2O; the cobalt salt is CoCl2·6H2O; the molar ratio of the nickel element in the nickel salt, the cobalt element in the cobalt salt and urea is 1:2:
3.
4. The preparation method according to claim 1 or 3, characterized in that: In step (1), the reaction temperature of the hydrothermal method is 120-160° C., and the reaction time is 4-12 h.
5. The preparation method according to claim 1, characterized in that: In step (2), the reaction temperature of the hydrothermal vulcanization method is 120-160° C., and the reaction time is 4-12 hours.
6. The preparation method according to claim 1, characterized in that: In step (3), the obtained NiCo2S4@NF is treated with hydrazine hydrate to obtain a sulfur vacancy V s -NiCo2S4@NF is specifically: the obtained NiCo2S4@NF is immersed in a N2H4·H2O solution and allowed to stand for 2-12 minutes.
7. The preparation method according to claim 1, characterized in that: In step (4), the molar volume ratio of Ni(NO3)2·6H2O, terephthalic acid and solvent is 0.3mmol:0.2mmol:25ml; and the solvent is N,N-dimethylformamide.
8. The preparation method according to claim 1 or 7, characterized in that: In step (4), the reaction temperature of the hydrothermal reaction is 120-160° C., and the reaction time is 1-12 h.
9. The high specific energy V prepared by the preparation method according to any one of claims 1 to 8 s -NiCo2S4@Ni-MOF self-supporting electrode.
10. A supercapacitor, characterized in that: The raw material includes the high specific energy V as claimed in claim 9 s -NiCo2S4@Ni-MOF self-supporting electrode.
